2010
DOI: 10.1007/s11033-010-0071-9
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1α inhibits hypoxia and serum deprivation-induced apoptosis in mesenchymal stem cells through PI3K/Akt and ERK1/2 signaling pathways

Abstract: Bone marrow-derived mesenchymal stem cells (BMSCs) have been demonstrated to be a promising cell sources for cardiac regeneration. Poor survival rate of transplanted BMSCs in infarcted myocardium attenuated its clinical application. It's reported that stromal-derived factor-1 (SDF-1) could protect progenitor cells including endothelial progenitor cells and embryonic stem cells from apoptosis. But little is known whether SDF-1α protein has the same protective effects on BMSCs under conditions of hypoxia and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…A recent report shows that SDF-1a-mediated PI3K/AKT and ERK1/1 signaling can prevent hypoxia-induced apoptosis in bone marrow-derived mesenchymal stem cells. 52 Whether similar mechanisms can occur in this tumor model requires further investigation, although we have found that the monocytic cell line, Raw264.7, in ALTS1C1 CM was more resistant to hypoxic stress than in SDF kd CM. As reported, 10,53 various subtypes of TAMs have different effects on tumor growth and prognosis.…”
Section: Sdf-1 Promotes Glioma Invasion and Tam Tropism S-c Wang Et Almentioning
confidence: 86%
“…A recent report shows that SDF-1a-mediated PI3K/AKT and ERK1/1 signaling can prevent hypoxia-induced apoptosis in bone marrow-derived mesenchymal stem cells. 52 Whether similar mechanisms can occur in this tumor model requires further investigation, although we have found that the monocytic cell line, Raw264.7, in ALTS1C1 CM was more resistant to hypoxic stress than in SDF kd CM. As reported, 10,53 various subtypes of TAMs have different effects on tumor growth and prognosis.…”
Section: Sdf-1 Promotes Glioma Invasion and Tam Tropism S-c Wang Et Almentioning
confidence: 86%
“…Yin et al showed that addition of 0.5-2 mg/ml of SDF-1 inhibited hypoxia and serum deprivation-induced apoptosis of MSCs. 66 The effect was abolished by PI3K inhibitor wortmannin, indicating the important role of the PI3K/Akt pathway in SDF-1-increased MSC survival.…”
Section: The Pi3k/akt Pathway and Survival Ability Of Mscsmentioning
confidence: 93%
“…Stromal cell-derived factor-1 (SDF-1) has been shown to increase MSC survival by several studies. [66][67][68] Liu et al demonstrated that SDF-1 can increase the resistance of MSCs to apoptosis induced by H 2 O 2 . 39 The pretreatment of MSCs with SDF-1 significantly reduced apoptosis by activating the PI3K/Akt pathway.…”
Section: The Pi3k/akt Pathway and Survival Ability Of Mscsmentioning
confidence: 99%
“…26,27 Many studies have shown that some clinical chemotherapeutic agents could induce cancer cell apoptosis via regulating MAPKs and Akt kinase activity. [28][29][30] To determine the role of these kinases in tetrandrine-induced HCC apoptosis, Western blot analysis was used to evaluate the activity of MAPKs and Akt-related proteins after tetrandrine treatment. Cancer Therapy The results showed that phosphorylated levels of ERK1/2, JNK and Akt decreased after tetrandrine treatment, but there was no significant change in phospho-p38 protein level (Fig.…”
Section: Tetrandrine Induces Hcc Cell Apoptosis Through Inhibition Ofmentioning
confidence: 99%